On the Parental Influence on Children’s Physical Activities and Mental Health During the COVID-19 Pandemic - Khozaei, Fatemeh; Carbon, Claus-Christian (Frontiers in Psychology, 2022)
Background: While neighborhood safety and stranger danger have been mostly canonized to play a part in parents’ physical activity (PA) avoidance, little is known about the impact of parental stress and perceived risk on children’s physical activity avoidance and consequently on children’s level of physical activity and wellbeing. Understanding the contributors to children’s wellbeing during pandemic disease is the critical first step in contributing to children’s health during epidemic diseases. Method: The current study employed 276 healthy children, aged 10 to 12 years old, and their parents (552 in total). Data was collected in October and November 2020, about nine months after the local closing of schools due to the COVID-19 pandemic. Parents and children answered a separate set of questions. Besides the demographic information, the parents answered questions on their stress level, perceived risk of COVID-19, and PA avoidance for children. Children responded to questions on their physical activity and wellbeing in the last week. Data were analyzed using SmartPLS. Result: The result of the study supported the four directional research hypotheses of the sequential study model. As it was hypothesized, parents’ stress and perceived risk levels of COVID-19 negatively affected children’s PA. The PA level was shown to predict children’s wellbeing and mental health. Conclusion: The current study sheds light on parents’ role in children’s wellbeing and mental health during the COVID-19 pandemic. Parents with higher stress and high restrictive behaviors might put their children at risk of mental disorders in the end.